AI Camera: A Unique Technology for Shopping Centers with Super Personalization - Gupta, Granthana Sen (Journal of Research in Science and Engineering, 2025)
This article is about making shopping experiences more personalized using hyper AI technology in retail malls. This could be achieved by using IndoAI AI cameras. Here hyper AI personalization combines facial recognition technology and real - time advertising to create a unique shopping experience for each customer. The article explains the main elements of this framework and shows how Mall used it to improve customer satisfaction. By using IndoAI's advanced facial recognition system, Mall will able to show ads tailored to each customer's preferences and behavior. This proposed case study shows that hyper AI personalization can make a big difference in retail, helping stores connect better with customers and grow their business. As the retail industry continues to evolve, innovations in AI - powered personalization will play a crucial role in shaping the future of customer engagement and satisfaction.